The Future of the Transition to Islamic Banking in Libya (A Field Study on Al-Jumhuriya Bank and Bank of Commerce and Development) (Journal of human and social sciences, 2022)
The banking system is considered one of the most effective systems capable of achieving economic stability amid global economic fluctuations. This has led traditional commercial banks to compete in offering Islamic banking services. The problem of this study lies in the fear of Libyan banks that the Islamic banking transition project may fail due to the numerous challenges and obstacles it faces. The study aims to explore the opinions and expectations of bank officials and managers regarding the future of the transition to Islamic banking in Libya. The importance of this study stems from its potential to enrich the scientific literature and provide new data and insights for researchers and stakeholders interested in this topic. The study concluded that the future of the transition to Islamic banking in Libya is expected to be positive.
Keywords: Islamic Banking; Banking Transition; Libyan Bank; Al-Jumhuriya Bank, Bank of Commerce and Development